2003
DOI: 10.1021/es0201449
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Soot Carbon on the Soil−Air Partitioning of Polycyclic Aromatic Hydrocarbons

Abstract: Soil-air partitioning is one of the key processes controlling the regional and global cycling and storage of polycyclic aromatic hydrocarbons (PAHs). However, the specific processes dominating the partitioning of PAHs between these two environmental compartments still need to be elucidated. Stable and distinct atmospheric conditions paralleling different soil properties are found at Tenerife island (28 degrees 18'N, 16 degrees 29'W), which is located in permanent inversion layer conditions, and they provide in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
47
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(52 citation statements)
references
References 47 publications
4
47
1
Order By: Relevance
“…The values measured in the present study were similar to these, however, they were higher than those typically assumed in modeling studies (10-20%) [22,35]. It was assumed that a EC /a AC ¼ 1, f OM ¼ 1.6 f OC , and f OC /f EC ¼ 3 where f OC is the fraction of total organic carbon [39,42]. Dachs et al [43] have suggested that the thermodynamics-based model recently reported by van Noort [44] can be used to estimate K SA values for PAHs as a function of supercooled liquid vapor pressure (P L , Pa) and elemental carbon specific surface area (a EC , m 2 g À1 ):…”
Section: Gas-particle Partitioningsupporting
confidence: 84%
“…The values measured in the present study were similar to these, however, they were higher than those typically assumed in modeling studies (10-20%) [22,35]. It was assumed that a EC /a AC ¼ 1, f OM ¼ 1.6 f OC , and f OC /f EC ¼ 3 where f OC is the fraction of total organic carbon [39,42]. Dachs et al [43] have suggested that the thermodynamics-based model recently reported by van Noort [44] can be used to estimate K SA values for PAHs as a function of supercooled liquid vapor pressure (P L , Pa) and elemental carbon specific surface area (a EC , m 2 g À1 ):…”
Section: Gas-particle Partitioningsupporting
confidence: 84%
“…The a EC value (62.7 m 2 g À1 ) was taken from a recent study by Jonker and Koelmans (2002). It was assumed that a EC /a AC ¼ 1, f OM ¼ 1.6f TOC , and f OC /f EC ¼ 3 where f TOC is the fraction of total organic carbon (Dasch and Eisenreich, 2000;Ribes et al, 2003). Under these assumptions, modeled K p values were calculated using Eq.…”
Section: ð15þmentioning
confidence: 99%
“…For instance, BC may be an important component of sedimentary carbon preservation (Goldberg 1985;Gustafsson and Gschwend 1998;Masiello and Druffel 1998;Dickens et al 2004) and thereby constitutes a valuable record of the global fire history (e.g., Bird and Cali 1998). Sorption of aromatic compounds to BC is 10 to 1000 times stronger than to nonpyrogenic sedimentary organic matter (e.g., Bucheli and Gustafsson 2000;Accardi-Dey and Gschwend 2002;Jonker and Koelmans 2002;Cornelissen and Gustafsson 2004) and frequently governs the environmental distribution of many organic pollutants (Gustafsson et al 1997;Gustafsson and Gschwend 1997;Dachs and Eisenreich 2000;Persson et al 2002;Ribes et al 2003). In the atmosphere, BC affects Earth's radiative heat balance (e.g., Jacobson 2001) and BC in urban air particles has been implicated as the culprit of epidemiological respiratory diseases and human deaths (Dockery et al 1993;Künzli et al 2000;Gerde et al 2001).…”
mentioning
confidence: 99%